Insight into the Interactions between Novel Coumarin Derivatives and Human A3 Adenosine Receptors. Issue 10 (18th July 2014) - Matos, Maria João; Vilar, Santiago; Kachler, Sonja; Fonseca, André; Santana, Lourdes; Uriarte, Eugenio; Borges, Fernanda; Tatonetti, Nicholas P.; Klotz, Karl‐Norbert
Abstract A study focused on the discovery of new chemical entities based on the 3‐arylcoumarin scaffold was performed with the aim of finding new adenosine receptor (AR) ligands. Thirteen synthesized compounds were evaluated by radioligand binding (A1, A2A, and A3) and adenylyl cyclase activity (A2B) assays in order to study their affinity for the four human AR (hAR) subtypes. Seven of the studied compounds proved to be selective A3AR ligands, with 3‐(4′‐methylphenyl)‐8‐(2‐oxopropoxy)coumarin (12) being the most potent (Ki=634 nM). None of the compounds showed affinity for the A2B receptor, while four compounds were found to be nonselective AR ligands for the other three subtypes. Docking simulations were carried out to identify the hypothetical binding mode and to rationalize the interaction of these types of coumarin derivatives with the binding site of the three ARs to which binding was observed. The results allowed us to conclude that the 3‐arylcoumarin scaffold composes a novel and promising class of A3AR ligands. ADME properties were also calculated, with the results suggesting that these compounds are promising leads for the identification of new drug candidates.